Rumah Nada Recording Experience Event Organizer's Promotional Mix Strategy for the 2024 Titik Temu Festival via Instagram @Festivaltitiktemu (JPS: Journal of Publicness Studies, 2025)
This study aims to examine how the Promotion Mix Strategy of the RNR Experience Event Organizer in increasing visitor interest in the Implementation of the 2024 Titik Temu Festival through Instagram @festivaltitiktemu. The main function of the Titik Temu Festival is as a festival medium that firmly promotes and supports the local ecosystem in Central Sulawesi. The theory used in this study is the Promotion Mix Promotion Mix consisting of Advertising, Sales Promotion, Face-to-Face Sales Personal Selling, Direct Marketing and Public Relations by Kotler and Keller. The subjects of this study were the Event organizer Rumah Nada Recording Experience as the activity manager and the manager of the @festivaltitiktemu Instagram account. The 2024 Titik Temu Festival was chosen as the focus of the study, because it is the most recent implementation, also proving that this activity has been consistently held for three consecutive years. The method in this study is using the Descriptive Qualitative method. This study uses a resource selection technique with a Purposive sampling approach involving three people as Project Leader, Project Manager and Program Manager. Data collection techniques are carried out by means of observation, in-depth interviews and documentation. Data analysis techniques use qualitative analysis consisting of data reduction. Data presentation, verification. The results of the study How the Promotion Mix Strategy of the RNR Experience Event Organizer in increasing Visitor Interest in the Implementation of the 2024 Titik Temu Festival Activities Through Instagram @festivaltitiktemu has been running well, but has not been optimal in the use of direct marketing promotion mix Direct Marketing using Broadcast messages or automatic message systems on existing customer data in previous years is not used at all, information on telephone numbers, emails, customer Instagram accounts is easily obtained, sending automatic messages, promotional messages and so on can reach the heads of potential customers more quickly.
Keywords: Marketing Communication Strategy, Promotional Mix Strategy, Social Media